Integrating E-business models for government solutions citizen-centric service oriented methodologies and processes - Chhabra, Susheel.; Muneesh Kumar. (Advances in electronic government series, 2009)
This book provides a collection of essential tools and alternative e-business strategies that can be incorporated into e-government solutions. The goal is to help in evolving effective methodologies and processes and consequently provide cost effective and citizen-centric services. Useful to scholars, researchers, and academic institutions, this book will enable readers to examine current issues and promote research initiatives to improve service delivery in e-government.